"We Know for a Fact": Dyslexia Interventionists and the Power of Authoritative Discourse. (September 2018) - Worthy, Jo; Svrcek, Natalie; Daly-Lesch, Annie; Tily, Susan
Although researchers have studied dyslexia for over a century, there is still much debate about how dyslexia differs from other reading difficulties and how to support students labeled dyslexic. Nevertheless, dyslexia policy and practice are steeped in authoritative discourse that speaks of a definitive definition, unique characteristics, and prescribed intervention programs that are not well supported by research. In Texas, and increasingly in other states, only educators trained in these programs are considered qualified to provide intervention for students identified as dyslexic. In contrast to earlier research, which found that the word dyslexia decreased teachers' confidence and feelings of self-efficacy, the dyslexia interventionists we interviewed expressed a high degree of confidence and certainty about dyslexia and the interventions they used. Bakhtin's notion of authoritative and internally persuasive discourse helped us think about the reasons for these findings and how to initiate a broader and more inclusive conversation about dyslexia.